Nipple-sparing mastectomy in patients with BRCA 1/2 mutations and variants of uncertain significance - Manning, A. (Br J Surg, 2015)
BACKGROUND: Nipple-sparing mastectomy (NSM) is associated with improved cosmesis and is increasingly performed. Its role in BRCA mutation carriers has not been well described. Here indications and outcomes of BRCA mutation carriers undergoing NSM are studied. METHODS: BRCA mutations carriers who underwent NSM were identified. Details of patient demographics, surgical procedures, complications, and relevant disease stage and follow-up, were recorded. RESULTS: 177 NSMs were performed on 89 BRCA mutation carriers between 9/2005–12/2013. 26 patients (median age 41 years) had NSM for early-stage breast cancer, and a contralateral prophylactic mastectomy (CPM). Mean tumor size was 1.38cm (range 0.1–3.5cm). 63 patients had NSM for prophylaxis (median age 39 years), 8 of whom had an incidental diagnosis of DCIS. In the 26 breast cancer patients, at median follow-up of 2.34 years (interquartile range (IQR) 0.45–6.06), there were no local or regional recurrences. In the 63 patients undergoing prophylactic NSM, at median follow-up of 2.15 years (IQR 0.11–8.14), there were no newly diagnosed breast cancers. All patients had immediate breast reconstruction. Five patients (5.6%) required subsequent excision of the nipple-areolar complex for oncological concerns or other reasons. Skin desquamation occurred in 68 of 177 breasts (38.4%) and resolved without intervention. Flap necrosis requiring debridement occurred in 13/177 breasts (7.3%), and tissue-expander or implant removal was necessary in 6 cases (3.4%). CONCLUSION: Nipple-sparing mastectomy is an acceptable choice for patients with BRCA mutations, with no evidence of compromise to oncological safety at short-term follow-up. This report shows an acceptable complication rate, and patients rarely required subsequent excision of the nipple-areolar complex.